A Study of Parasitic Ticks That Affects Buffaloes in DHI-QAR and Al-Muthanna Governorates/Iraq - Mohammed. J. Falih, Abbas. K. Hamza (Pakistan Journal of Medical & Health Sciences, 2022)
In this study about 140 of different ages buffaloes and from different regions of Dhi-Qar and AL-Muthanna governorates were examined to diagnose their infection with ticks, as well as to determine the prevalence of these infections. Samples were collected from early of October 2021until late of February 2022 along five months. From 140 buffaloes the infection with ticks found in 67 (47.85%) percentage, and the higher proportion was in Dhi Qar governorate (48.71%), while the infection rate of Al-Muthanna governorate was about (46.77%). During this study four types of ticks were obtained, arranged according to the following ratios, Hyalomma. anatolicum showed a highest percentage (45.66%), H.marginatum (31.21%), H.dromedarii (16.76%), and H.scupense (6.35%), since the latter recorded the lowest percentage. The study also showed that the most susceptible part of the buffaloes body was the head and back in a ratios of 45.08%, 40.46% respectively, while the space between legs recorded the lowest susceptible part to these infections in a ratio of 1.73% . Keywords: buffaloes, parasitic ticks, Dhi-Qar